Effect of Traditional Textile Techniques on Modern Fashion Design in Nigeria - Ibrahim, Suleiman (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the effect of traditional textile techniques on modern fashion design in Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Traditional textile techniques in Nigeria, such as adire (tie-dye), akwete weaving, and aso-oke fabric, have significantly influenced modern fashion design. These indigenous methods, known for their intricate patterns and vibrant colors, are increasingly incorporated into contemporary fashion by Nigerian designers. The use of traditional techniques adds cultural depth and authenticity, appealing to both local and international audiences. Modern designers blend these age-old methods with contemporary styles, creating innovative and unique fashion pieces that reflect Nigeria’s rich heritage. This fusion has not only revitalized traditional craftsmanship but also positioned Nigeria as a global hub for Afrocentric fashion. Unique Contribution to Theory, Practice and Policy: Cultural identity theory, sustainable fashion theory & brand equity theory may be used to anchor future studies on the effect of traditional textile techniques on modern fashion design in Nigeria. Fashion designers should collaborate with local artisans who specialize in traditional textile techniques. Policymakers should develop initiatives that support artisanal communities involved in traditional textile production.